Structure of transitional layer forming in Mo-Si system by P+ ion implantation over molybdenum film - Yu. P. Snitovsky; L. P. Khodarina (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Questions of the implantation fluency of Si(111) by phosphorus ions influence, the effect of post-implant annealing of Si implantation and an annealing of Mo-Si system and of irradiation by phosphorus ions of generated ohmic contact of system Mo-Si and an annealing at low temperatures on the structure and phase composition of transitional layer have been considered.